2018
DOI: 10.1186/s12970-018-0236-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ketogenic diet on body composition during resistance training in trained men: a randomized controlled trial

Abstract: BackgroundKetogenic diets (KD) have become a popular method of promoting weight loss. More recently, some have recommended that athletes adhere to ketogenic diets in order to optimize changes in body composition during training. This study evaluated the efficacy of an 8-week ketogenic diet (KD) during energy surplus and resistance training (RT) protocol on body composition in trained men.MethodsTwenty-four healthy men (age 30 ± 4.7 years; weight 76.7 ± 8.2 kg; height 174.3 ± 19.7 cm) performed an 8-week RT pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 56 publications
4
56
1
4
Order By: Relevance
“…Our study aimed to evaluate the effect of a KD on body composition and strength following an 8-week RT program in strength-trained women. In light of results obtained in men under similar conditions [17], we hypothesized that a KD combined with RT would not alter FFM or strength-related parameters in strengthtrained women; the results obtained partially support our hypothesis. The use of reagent strips for the qualitative assessment of ketosis state was necessary in this study given the design and resource limitations.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our study aimed to evaluate the effect of a KD on body composition and strength following an 8-week RT program in strength-trained women. In light of results obtained in men under similar conditions [17], we hypothesized that a KD combined with RT would not alter FFM or strength-related parameters in strengthtrained women; the results obtained partially support our hypothesis. The use of reagent strips for the qualitative assessment of ketosis state was necessary in this study given the design and resource limitations.…”
Section: Discussionsupporting
confidence: 58%
“…Compared to endurance training, few studies have specifically investigated the effects of a KD on body composition and strength levels in resistance-trained subjects undertaking a resistance training (RT) program. It was previously reported that an eight-week RT program accompanied by a KD reduced fat mass (FM) and preserved fat-free mass (FFM) in trained men [17]. Similarly, other studies have shown favorable changes in body composition (↑ FFM and ↓ FM), strength and total testosterone [18].…”
Section: Introductionmentioning
confidence: 92%
“…While the current literature on athletic populations is inconclusive, it is important to acknowledge that several studies conducted on non-athletic individuals have demonstrated that Lean body mass (LBM) tends to be retained following a KD [ 21 , 22 , 23 ]. A study on 10 healthy men demonstrated that adherence to a KD over 6 weeks resulted in retention of LBM at week three followed by an increase at week six [ 23 ]. This may be due to the energy (29 kcal/kg/day) and protein intakes (2 g/kg/day) that were maintained by participants throughout the duration of this study [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on 10 healthy men demonstrated that adherence to a KD over 6 weeks resulted in retention of LBM at week three followed by an increase at week six [ 23 ]. This may be due to the energy (29 kcal/kg/day) and protein intakes (2 g/kg/day) that were maintained by participants throughout the duration of this study [ 23 ]. On the basis of these findings, it is suggested that future studies on athletic populations concentrate on protein intake or other supplementation (e.g., creatine or leucine) to ensure adequacy for LBM retention and/or increases when commencing a KD.…”
Section: Discussionmentioning
confidence: 99%
“…And not less important: at the beginning the patients report about drowsiness, dizziness, fatique, insomnia, light nauseas, constipation -all symptoms that were named "keto-flu" but they normally lessen (26). Important: patients can continue physical training despite of limitation of carbohydrates (176,177).…”
Section: K E T O G E N I C D I E T F O R R E D U C T I O N O F W E I mentioning
confidence: 99%